Post traumatic facial artery pseudoaneurysm-A case report - Raisa Altaf; Imtiaz Ali; Rabiya Siraj; Jawaid Iqbal; Faiza Hassan (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Facial artery a branch of external carotid artery rarely develops an aneurysm due to its superficial location and small size that mostly leads to complete dissection rather than laceration of the vessel. Pseudo-aneurysms develop in the superficial temporal arteries in this region. Rupture of this aneurysm can lead to extravasation of blood within the adjacent soft tissues resulting in hemorrhage in some cases. Only a few cases of facial artery aneurysms have been reported in publications. We are therefore discussing here a case of left facial artery pseudoaneurysm secondary to trauma and its radiological imaging findings on CT angiogram.